Geriatric emergencies - Murdoch, Iona, 1984-; Turpin, Sarah, 1985-; Johnston, Bree; MacLullich, Alasdair; Losman, Eve (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2015)
Geriatric Emergencies is a practical guide to the common conditions affecting older patients who present in an emergency to hospital or primary care.Beginning with the essentials of history taking and clinical examination, the book covers a comprehensive range of emergencies, emphasizing the different management approaches which may be required in older patients. Common geriatric presentations such as falls, delirium and stroke, are explored in detail in addition to more diverse topics such as abdominal pain, major trauma and head injury. Ethical considerations such as advanced care planning, palliative care and capacity assessment are discussed with practical tips on communicating with patients and their relatives.Geriatric Emergencies provides concise up-to-date guidance to the emergency management of the older patient. It is a recommended resource for all health professionals working in the acute environment, in which a large proportion of patients are aged over 65
Introduction to geriatric emergency medicine -- Essentials of assessment and management in geriatric emergency medicine -- Special skills in geriatric emergency medicine -- Vulnerable adults and elder abuse -- Chest pain and atrial fibrillation -- Dyspnoea -- Infection and sepsis -- Falls and immobility -- Syncope -- Dizziness -- Major trauma -- Fractures and back pain -- Skin trauma -- Head injury -- Abdominal emergencies -- Diabetic and environmental emergencies -- Acute kidney injury and metabolic emergencies -- Delirium -- Stroke and transient ischaemic attack
BIBINDX
Keywords: Emergencies; Aged; Emergency Treatment -- methods; Emergency medicine; Geriatrics; Electronic books